Hafez Ibrahim's translation of the monologue of the dagger in Shakespeare's Macbeth - Aziz, Amal Gouda Abdel (Linguistics and Culture Review, 2021)
One of the most challenging and multifaceted tasks a translator can do is translating poetry. This is because form and content in poetry have a distinct and interdependent relationship that allows the reader to experience a unique emotional reaction. Reproducing the same emotional effect on the TT reader is the most controversial aspect, resulting in the widespread assumption among scholars that poetry is untranslatable. Poetry translation needs more effort and creativity to convey the beauty and power of the style as well as the intended message of the ST. The main aim of the present study is to analyze Hafez Ibrahim's poetic translation into Arabic of the famous soliloquy of the protagonist in the scene of the dagger in Shakespeare's play, Macbeth. Employing a descriptive-analytical approach to compare the ST and TT texts, the study arrived at the conclusion that the translator was adequately successful in keeping the subject matter, the general atmosphere, and the tone of the original text. On the other hand, he chose to "Arabize" the metaphorical language of Shakespeare to make it closer to Arab readers' sensibilities.